Pilot Plant Production of Wrapping Papers from a Mixture of Oaks - Guha, S. R. D.; Mathur, G. M.; Sharma, Y. K.; Kumar, Krishan (Indian Forester, 1970)
Pilot plant scale trials on manufacture of wrapping papers from a mixture of three species of Oaks, viz., Quercus semecarpifolia, Quercus dilatata and Quercus incana are described. Pilot plant scale trials confirm the laboratory results published earlier. The trials on beating indicate that beater equipped with basalt lava roll and basalt lava bed plate gives better results than beater equipped with phosphorbronze tackles on the roll. The results show that for the same freeness, the percentage of fibres retained on 48 mesh were higher and percentage of fines (passing through 150 mesh) were lower when beating was done with basalt lava roll and basalt lava bed plate.